Qualitative C-reactive protein as a marker of neonatal sepsis in a tertiary neonatal unit in Sudan - Abdelmoneim E. Kheir; Ghada A. Jobara; Kamal M. Elhag; Mohamed Z. Karar (Healthcare in Low-resource Settings, 2013)
Sepsis is one of the most common causes of morbidity and mortality in newborns. Diagnosis of neonatal sepsis may be difficult because clinical presentations are often non-specific. The aim of this study was to evaluate the role of qualitative C-reactive protein in the diagnosis of neonatal sepsis, and examine the correlation between C-reactive protein, blood culture and risk factors for sepsis. This was a prospective study, conducted in the Neonatal Intensive Care Unit at Soba University Hospital, Sudan. A total of seventy babies with a clinical diagnosis of sepsis were included. Chi square test was used to determine the association between C-reactive protein and risk factors for sepsis and also the association between C-reactive protein and blood culture. Blood culture was positive in 41.4% of babies, and C-reactive protein was positive in 58% of babies with positive blood culture. There was significant association between C-reactive protein results and blood culture (P=0.00). In conclusion, we can assume that Creactive protein is a reliable diagnostic marker of neonatal sepsis, especially in developing communities with poor resources.